The effectiveness of Reinvestment Allowance (RA) and Tax Attributes in stimulating the performance of incentivised firms: moderating effects of foreign directorship / Fairus Halizam A. Hamzah - A. Hamzah, Fairus Halizam (Faculty of Accountancy, 2019)
The debate on the implication of fiscal incentives is extensive. Nevertheless, whether tax incentives succeed in stimulating firm performance remains highly controversial and has received much attention from governments and policymakers. We aimed at providing evidence about the effect of RA and other tax attributes on firm performance. Secondly, we examined if firm directorship has a moderating effect on our regression estimation. To fully understand the effects of fiscal incentives, a systematic study is needed to link RA to not just business location, employment, economic implication development but also to the overarching issues of firm performance and growth. This research uses the Panel Least Square regression model to examine the interplay between RA and other tax attributes on firm-level performance measured by return on asset. Employing tax return data from 2007 to 2016 of corporate firms consistently claiming RA, this research affirms that RA has positively impacted the performance of incentivised firms in Malaysia. Besides RA, these incentivised firms also depend on other tax attributes such as lower effective tax rate, various tax benefits, the firm scale of operation as well as adequate tax audit monitoring. We also affirm that foreign directorship only moderates one of the tested explanatory variables used in this research, which is the effective tax rate (ETR). Overall, the evidence in this research-driven extensively by responses of the incentivised firms which addresses the issue of effective incentive utilisation and tax attributes. This research could be the first to contribute evidence on the systematic assessment of RA.